Recurrent Priapism From Cabergoline and Bromocriptine in a Hypogonadal Man With Prolactinoma - Lakshmi P. Menon MD; Wedad Rahman MD (SAGE Publishing, 2021)
Dopamine agonists are generally well tolerated and represent the first-line therapy for prolactinomas. We report a case of a 20-year-old man with a macroprolactinoma who developed recurrent priapism with cabergoline and bromocriptine. Transsphenoidal pituitary adenoma resection was done with normalization of the prolactin level. Priapism is a rare side effect of dopamine agonists that warrants discontinuation of therapy. Patients should be educated about this potential side effect at the time of prescribing the medication.